Tanggung Jawab Kejaksaan Terhadap Pengembalian Kerugian Keuangan Negara Oleh Pelaku Tindak Pidana Korupsi - Teddy Lazuardi Syahputra; Madiasa Ablisar; Mahmud Mulyadi; Muhammad Ekaputra (Universitas Sumatera Utara, 2019)
Abstract. In principle, the return of state financial losses by perpetrators of corruption is far more beneficial than punishing the perpetrators. Jampidsus Circular Number B-1113/F/ Fd.1/ 05/2010 concerning Priorities and Achievements in Handling Corruption Crime Cases, and Jampidsus Letter Number 765/F/Fd.1/04/2018 concerning Technical Guidelines for Handling Criminal Cases Corruption The Investigation Stage is a form of prosecutor's discretion which prioritizes the return of state financial losses because it can be useful for the inclusion of a budget for the receipt of state expenditure through non-tax state revenues from prosecutors. The problem raised in this research is how is the legal basis of the Republic of Indonesia's Attorney General's Office in making policies related to handling and settling cases of corruption in Indonesia, the authority possessed by investigating prosecutors towards relatively small perpetrators of corruption in the case of criminal offenders restore the state's financial losses and the responsibility of the investigating prosecutor in carrying out discretion against the perpetrators of corruption in the case of small amounts of state financial losses. To find answers to these problems, this study uses a type of normative legal research that is descriptive analytical, where normative legal research uses secondary data as the main data by using data collection techniques carried out by means of library research (library reseacrh), and data analysis using methods qualitative data analysis. Keywords: Responsible, Returns, Losses, State Finance.